Social Facts as Depicted in The Girl from the Coast Novel - Yuliana, Rizkia (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Social facts are often found in society. Although, often people do not understand and are also aware of it. Social facts are coercive. In addition, the action has existed and been carried out since ancient times and is still being carried out today. Thus, in dealing with social facts, individuals must realize that is a rule or even an obligation that must be carried out and if not carried out, then the individual will receive punishment or even social rejection. Therefore, the aims of this thesis are (1) to find out what kinds of social facts exist in the novel The Girl from the Coast. Then, (2) to find out how the characters in The Girl from the Coast face the social facts. This thesis uses the Literary Criticism method with the Sociological approach. Then, in outline, this thesis uses the theory of social facts by Emile Durkheim. Thus, the results obtained are (1) Several forms of social facts in the novel The Girl from the Coast by Premoedya Ananta Toer; a) Material. From the material form, there are several forms of social facts found in the novel, such as marriage, work, Javanese culture, and Islamic sharia. b) Non-Material. For the non-material form, there is only one form found in the novel, that is egoism. (2) How the characters in The Girl from the Coast novel by Pramoedya Ananta Toer face the social facts by Emile Durkheim. Therefore, readers can make this novel as material for research using topics other than social facts, such as psychology of literature or other theories. Keywords: Social Fact, Sociology of Literature, The Girl from the Coast